Hair Love - Cherry, Matthew A.; Harrison, Vashti (New York : Kokila, 2019)
"It's up to Daddy to give his daughter an extra-special hair style in this ode to self-confidence and the love between fathers and daughters"--
Keywords: Hair -- Juvenile fiction; Self-confidence -- Juvenile fiction; African American girls -- Juvenile fiction; African Americans -- Juvenile fiction; Fathers and daughters -- Juvenile fiction; Hair -- Fiction; Self-confidence -- Fiction; African American girls -- Fiction; African Americans -- Fiction; Fathers and daughters -- Fiction; Picture books